The Word Sorts Strategy - Novarisany Sabarlele; Orpa Penina Oraile (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2022)
This study discussed the use of Word Sort Strategy as a tool in teaching vocabulary. Teaching vocabulary is essential in language learning. The teacher should be able to use appropriate ways for teaching vocabulary so that the students can learn effectively Harmer, as cited in Yulianto 2010:19-20). Most of the students consider that learning vocabulary is difficult so that they lack interest and motivation. Students sometimes could only say and understand some words and could not develop their ideas well in their sentences. Therefore the teachers have a very important role to increase students’ motivation to learn supported by interesting ways as Word Sort Strategy. Word Sort Strategy contributes to increasing the students’ interest and motivation, making the students has a sense of the context of language and Word Sort can be a specific reference point. It can enhance students’ motivation in learning vocabulary.